Digital democracy: A systematic literature review - Congge, Umar; Guillamón, María-Dolores; Nurmandi, Achmad; Salahudin; Sihidi, Iradhad Taqwa (Frontiers in Political Science, 2023)
Digital democracy provides a new space for community involvement in democratic life. This study aims to conduct a systematic literature review to see the trend of concepts in the study of digital democracy. This study uses descriptive analysis with data sources derived from the Scopus database and processed with VosViewer. The results show three dominant concepts, namely democracy, internet, and movement. In addition, it was also found that the digital era provides positive benefits for democracy, the importance of public knowledge in quality digital democracy, and strong elite control in virtual democracy. This research contributes to showing the development and urgency of digital democracy. Meanwhile, the limitation is that the articles reviewed are only sourced from Scopus and no 2021 publications. Therefore, future studies require the use of a comparative analysis approach that uses the Web of Science (WoS) database and increases the duration of the latest search for articles.